Journal Notes - various authors (GDR Bulletin, 1981)
Reviews of: Connaissance de la RDA No. 12 (Patricia Herminghouse) Sinn und Form Vol. 33, No. 1-2 (Wolfgang Ertl) GDR Monitor No. 1-4 (Patricia Herminghouse) Neue Deutsche Literatur Vol. 29, No. 1-6 (Peter Beicken) Zeitschrift für Germanistik Vol. 1, No. 1-4, Vol. 2, No. 1-2 (Karl-Heinz Schoeps)